Answer:
6.36 s
Step-by-step explanation:
Here the free fall means that the object is subjected only to gravity force. there are no other acting forces
(Assume g = 9.8 ms⁻²)
This gravitational acceleration (g) is same through out the motion there for we can use motion equation symbols has usual meanings.
S = ut + 1/2 at²
where ,
- s - distance
- u - initial velocity
- a-acceleration
- t - time
↓S = ut + 1/2 at²
200 = 0.3 t + 1/2 × 9.8 × t²
4.9 t² + 0.3 t -200 = 0
Here you can have a quadratic equation and get a solution we can applie the formula to find the quadratic equation
Assume a quadratic equation be
ax² + bx +c =0
![solution (x) =\frac{-b+\sqrt{b^(2)-4ac } }{2a} or \frac{-b-\sqrt{b^(2)-4ac } }{2a}](https://img.qammunity.org/2020/formulas/physics/middle-school/i94mi8kfqqsisq37j4o0kx8rp1xt4v7lia.png)
t = -0.3 ±√0.3²-4×4.9×(-200) / (2×4.9)
t = 6.36 s or -6.42 s
but a time cannot be zero
therefore the solution should be 6.36 s